Collected Poems of John Shaw Neilson - Neilson, John Shaw (Australian Classics Library., 2013)
John Shaw Neilson (1872-1942) is Australia's great lyric poet. A new introduction by Dr Helen Hewson explores some of the influences which have shaped Neilson's poetry.